Rancang Bangun Buck Converter Menggunakan Kontrol Pi untuk Charging Baterai Pada Penerangan Gazebo - Erwanti, Nariyah Silviana; Sulistyowati, Riny; Febrianto, Zulfiyan (Prosiding Seminar Nasional Teknik Elektro, Sistem Informasi, dan Teknik Informatika (SNESTIK), 2024)
The amount of energy consumed is steadily rising. Solar, water, and wind energy are among the plethora of limitless energy sources. Solar energy is one of the energies that can be used in Indonesia. This is inextricably linked to Indonesia, which experiences tropical weather. One application for solar energy, which is renewable and ideal for use as an electricity source, is in gazebo. The gazebo is one of the amenities with open space that can be used as an alternative gathering place for various events. It appears that many gazebos do not yet have guest amenities like illumination and charging outlets. It was accomplished by developing a DC bus system. The device uses a 12 V/20 Ah battery as the energy source to charge two cellphones utilizing a DC light load of 12 V/5 W and a 5 volt power supply. A solar cell with a 20 watt output and a maximum voltage of 21,8 volts charges the battery. In order to obtain a constant voltage from the solar cell, a converter design that can lower the voltage is required. Thus, a converter design that can lower the voltage is required to obtain a constant voltage from the solar cell. The Buck Converter was the converter employed in this study. The converter's voltage should be regulated by the use of the PI control method in this study so that it can provide an output voltage with a set value. When the output voltage of the solar panel, which changes with temperature, irradiance, and other parameters, reaches a voltage setting point of 14,4 volts under PI control with the values of kp = 0,2 and ki = 668, the results for this tool are obtained.